In vitro Inhibitory Activity of Ethyl Acetate Extract of Symbiotic Bacteria Isolated from the Marine Sponge Haliclona fascigera against Multidrug Resistant Organism (MDRO) - Dian Handayani, Murniati Murniati, Rustini Rustini (Journal of Applied Pharmaceutical Science, 2016)
Increased use of antimicrobial irrational human and veterinary medicine causes increasing emergence of antibiotic resistant organisms or multidrug resistant organisms (MDRO). MDRO are common bacteria that have resistance to multiple types of antibiotics. The objective of the study was to determine the presence of antibacterial activity in the 26 ethyl acetate extracts of symbiotic bacteria from the marine sponge Haliclona fascigera against MDRO. The MDRO employed were Vancomycin-resistant Enterococcus sp (VRE), extended-spectrum-beta (β)- lactamase gram-negative organisms (ESBL), Carbapenem resistant Enterobacteriaceae (CRE) and Multi resistant Acinetobacter baumannii (MRAB). The susceptibility of MDRO against the extracts was determined using the disk diffusion method. The zone of inhibition was measured and expressed in millimeters. The results showed that nine ethyl acetat extracts that considered active to VRE and ESBL. The strongest inhibition activity was found in extract of Micrococcus sp.1 (M2R2) with MIC values of 0.625% against VRE.
Keywords: Multidrug resistant organisms (MDRO), Antibacterial activity, Symbiotic bacteria, Haliclona fascigera.